The inflammatory response seen when human omental adipose tissue explants are incubated in primary culture is not dependent upon albumin and is primarily in the nonfat cells - Tichansky David S; Cheema Paramjeet; Fain John N; Madan Atul K (BMC, 2010)
Abstract Background The present studies were designed to investigate the changes in gene expression during in vitro incubation of human visceral omental adipose tissue explants as well as fat cells and nonfat cells derived from omental fat. Methods Adipose tissue was obtained from extremely obese women undergoing bariatric surgery. Explants of the tissue as well as fat cells and the nonfat cells derived by digestion with collagenase were incubated for 20 minutes to 48 h. The expression of interleukin 1β [IL-1β], tumor necrosis factor α [TNFα], interleukin 8 [IL-8], NFκB1p50 subunit, hypoxia-inducible factor 1α [HIF1α], omentin/intelectin, and 11β-hydroxysteroid dehydrogenase 1 [11β-HSD1] mRNA were measured by qPCR as well as the release of IL-8 and TNFα. Results There was an inflammatory response at 2 h in explants of omental adipose tissue that was reduced but not abolished in the absence of albumin from the incubation buffer for IL-8, IL-1β and TNFα. There was also an inflammatory response with regard to upregulation of HIF1α and NFκB1 gene expression that was unaffected whether albumin was present or absent from the medium. In the nonfat cells derived by a 2 h collagenase digestion of omental fat there was an inflammatory response comparable but not greater than that seen in tissue. The exception was HIF1α where the marked increase in gene expression was primarily seen in intact tissue. The inflammatory response was not seen with respect to omentin/intelectin. Over a subsequent 48 h incubation there was a marked increase in IL-8 mRNA expression and IL-8 release in adipose tissue explants that was also seen to the same extent in the nonfat cells incubated in the absence of fat cells. Conclusion The marked inflammatory response seen when human omental adipose tissue is incubated in vitro is reduced but not abolished in the presence of albumin with respect to IL-1β, TNFα, IL-8, and is primarily in the nonfat cells of adipose tissue.